The effect of the implementation of occupational safety and health (K3) on the performance of factory employees at the Pagar Merbau palm oil plantation - Hifza Haridani; Eliska Eliska (Indonesian Journal of Health Science, 2026)
Occupational safety and health are closely related to employee performance, which can ensure the success of a company, as an efficient workplace environment directly influences employee performance. However, occupational safety and health issues in Indonesia have not received sufficient attention. This problem can be observed from the still high rate of workplace accidents in the country, particularly in the Pagar Merbau palm oil plantation. This study aims to determine the effect of occupational safety and health (OSH) on employee performance in the factory area of the Pagar Merbau Palm Oil Plantation. This a quantitative descriptive design with a survey approach using the total sampling method, involving all 60 factory employees as respondents. Data were collected through a questionnaire that had been tested for validity and reliability. The univariate analysis showed that the majority of employees assessed the implementation of OSH as good (93.3%), and most employees demonstrated good performance (86.7%). A simple linear regression analysis revealed that OSH had a significant effect on employee performance, with a significance value (p) = 0.000 and an R Square of 0.208, indicating that 20.8% of the variation in employee performance is explained by the OSH variable. Thus, proper implementation of OSH can significantly improve employee performance.